OPTIMIZATION PRODUCTION OF XYLANASE BY Bacillus pumilus IN EMPTY FRUIT BUNCH USING 3 L BIOREACTOR - Wijaya, Hans; Thontowi, Ahmad; Yopi, Yopi (LIPI Press, 2017)
Indigenous biomasses, such as empty fruit bunch, contain high xylan and are useful to produce raw xylanase, where this biomasses are very abundant in Indonesia. The focus of this research is to scale up the fermentation product into 3 litter feeds and to record the highest enzyme activity. Fermentation process has been done by using stirred fermentor MBI Winpact One Fermentation System. The isolate marine bacterium Bacillus pumilus has been used to degrade empty fruit bunch to produce raw xylanase. The result for different agitation speed showed that at 150 rpm has the highest xylanase activity. The effect of different aeration flows gives at a rate of 4 VVM achieved the highest enzyme activity and equal to 7.61 U/mL with cell growth equal to 2.06. The Sigma Antifoam C has been successfully being used as defoamer in the production fermentor and can be tolerated by Bacillus pumilus. The comparisons of different medium to generate different enzyme by Bacillus pumilus has achieved xylanase, mannanase, and cellulase, where xylanase has the highest enzyme activity among all of the enzymes produced.